Oxidative Stress and Antioxidant-Based Interventional Medicine in Ophthalmology - Claudia Honisch; Umberto Rodella; Claudio Gatto; Paolo Ruzza; Jana D'Amato Tóthová (MDPI AG, 2023)
The different anatomical compartments of the eye are highly subjected to reactive oxygen species (ROS) generation due to internal factors, such as metabolic high oxygen consumption, as well as environmental factors, including UV light. An antioxidant defense system is endowed in the eye tissues to regulate ROS quantity and activity. When this homeostatic system is overwhelmed, oxidative stress occurs, causing cellular damage, chronic inflammation, and tissue degeneration. It also plays a significant role in the development and progression of various ocular diseases. Understanding the mechanisms underlying oxidative stress in ocular conditions is thus crucial for the development of effective prevention and treatment strategies. To track marketed products based on antioxidant substances as active ingredients, the databases of the European Medicines Agency and the U.S. Food and Drug Administration were consulted. Only a limited number of items were identified, which were either used as therapeutic treatment or during ocular surgery, including antioxidants, synthetical derivatives, or pro-drugs designed to enhance tissue permeation and activity. This review aims to provide an overview of the primary ocular pathologies associated with oxidative stress and of the available pharmacological interventions centered around antioxidant molecules. Such insights are essential for advancing the development of effective prevention and novel treatment approaches.